2012
DOI: 10.5014/ajot.2012.003699
|View full text |Cite
|
Sign up to set email alerts
|

Methodology for the Systematic Reviews on Occupation- and Activity-Based Intervention Related to Productive Aging

Abstract: Systematic reviews of the literature relevant to community-dwelling older adults are important to the practice of occupational therapy. We describe the four questions that served as the focus for the systematic reviews of the effectiveness of occupational therapy interventions for older adults living in the community. This article includes the background for the reviews; the process followed for each question, including search terms and search strategy; the databases searched; and the methods used to summarize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
24
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 3 publications
0
24
0
Order By: Relevance
“…Performance outcomes included IADL performance and participation measurement tools as well as functional assessments, quality of life, and client-factor measures (such as muscle strength and self-efficacy) related to the performance of IADLs. Detailed information about the methodology and search terms for the review can be found in the article “Methodology for the Systematic Reviews on Occupation- and Activity-Based Intervention Related to Productive Aging” in this issue (Arbesman & Lieberman, 2012). …”
Section: Methodsmentioning
confidence: 99%
“…Performance outcomes included IADL performance and participation measurement tools as well as functional assessments, quality of life, and client-factor measures (such as muscle strength and self-efficacy) related to the performance of IADLs. Detailed information about the methodology and search terms for the review can be found in the article “Methodology for the Systematic Reviews on Occupation- and Activity-Based Intervention Related to Productive Aging” in this issue (Arbesman & Lieberman, 2012). …”
Section: Methodsmentioning
confidence: 99%
“…Studies were then further analyzed, categorized, and summarized according to established protocols. Detailed information about the methodology and a complete list of search terms for the entire project dedicated to productive aging can be found in "Methodology for the Systematic Reviews on Occupation-and Activity-Based Intervention Related to Productive Aging" in this issue (Arbesman & Lieberman, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…We used a grading system to evaluate the scientific evidence on the basis of the work of Sackett, Rosenberg, Muir Gray, Haynes, and Richardson (1996). Detailed information about the methodology for the entire evidence-based literature review and this particular focused question can be found in the article "Methodology for the Systematic Reviews on Occupation-and Activity-Based Intervention Related to Productive Aging" (Arbesman & Lieberman, 2012) in this issue.…”
Section: Methodsmentioning
confidence: 99%
“…Stav, W. B., Hallenen, T., Lane, J., & Arbesman, M. (2012). Systematic review of occupational engagement and health outcomes among community-dwelling older adults.…”
mentioning
confidence: 99%